2011
DOI: 10.1523/jneurosci.4287-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 Receptor Overexpression Alters Behavior and Physiology inDrd2-EGFPMice

Abstract: Bacteria artificial chromosome (BAC) transgenic mice expressing the reporter protein enhanced green fluorescent protein (EGFP) under the control of the D1 and D2 dopamine receptor promoters (Drd1-EGFP and Drd2-EGFP) have been widely used to study striatal function and have contributed to our understanding of the physiological and pathological functions of the basal ganglia. These tools were produced and promptly made available to address questions in a cell-specific manner that has transformed the way we frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 25 publications
5
96
1
Order By: Relevance
“…Several groups have reported alterations of DA transmission in certain BAC lines (Bagetta et al, 2012;Kramer et al, 2011); therefore, we measured brain tissue DA to ascertain whether our mouse model was normal or deficient in this respect. Importantly, we found no differences in the levels of DA or its metabolites in the caudate-putamen/nucleus accumbens region or the prefrontal cortex between the Th-EGFP mice and their littermates without the transgene.…”
Section: Gan-induced Glutamate Receptor Plasticitymentioning
confidence: 99%
“…Several groups have reported alterations of DA transmission in certain BAC lines (Bagetta et al, 2012;Kramer et al, 2011); therefore, we measured brain tissue DA to ascertain whether our mouse model was normal or deficient in this respect. Importantly, we found no differences in the levels of DA or its metabolites in the caudate-putamen/nucleus accumbens region or the prefrontal cortex between the Th-EGFP mice and their littermates without the transgene.…”
Section: Gan-induced Glutamate Receptor Plasticitymentioning
confidence: 99%
“…Recent studies have reported several behavioral and physiological alterations in drd2-eGFP mice (Kramer et al, 2011) that could influence opioid withdrawal. (Fig.…”
Section: Naloxone-precipitated Opioid Withdrawal Induces C-fos Expresmentioning
confidence: 99%
“…Nevertheless, caution in the interpretation of data resulting from the use of eGFP transgenic mice is needed since it has been indeed recently reported that D 2 R-eGFP mice express an altered behavioral and physiological phenotype due to D 2 receptor overexpression (Kramer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%